Investigating the impact of organizational culture on supply chain integration - Braunscheidel, Michael J.; Suresh, Nallan C.; Boisnier, Alicia D. (Human Resource Management, 2010)
AbstractSupply chain integration constitutes the major thrust of supply chain management initiatives. In this study, we investigate the effects of organizational culture to determine the types of cultural characteristics that are strongly associated with efforts to integrate the supply chain and delivery performance. Previous researchers have theorized and demonstrated that organizational culture leads to adopting management practices consistent with the culture and that these practices are associated with firm performance. There has been a relative dearth of research, however, on the impact of organizational culture in operations management literature. Thus, this study investigates the effects of organizational culture, measured by the competing values framework (CVF), on two types of supply chain integration efforts: (1) internal integration and (2) external integration with key suppliers and key customers. Employing the CVF, we assess organizational culture along four dimensions—market, hierarchy, clan, and adhocracy. Results indicate that culture does influence firms to adopt internal and external integration practices. Our findings also provide evidence that a firm's adhocracy culture score is positively associated with external integration, while a firm's hierarchy culture score is negatively associated with both internal and external integration practices. © 2010 Wiley Periodicals, Inc.